Manuscripts of the developer of the hanafia-maturidia religious tradition of the Turkic World in the World libraries - Shalkarov, D B (Journal of Oriental Studies, 2016)
The article considers keeping of the works of Husam al-din al-Syghnaqi «al-Kafi fi sharh usul al-fiqh li ‘Ali ibn Muhammad al-Bazdavi», «al-Nadzhah fi al-Tasrif fi ‘ilm al-Sarf», in the World libraries and his teachers. Hafiz al-din al-Kabir Muhammad ibn Nasr, Fahr al-din al-Maimargi Muhammad ibn Muhammad ibn Iliyas.